Knowledge of mental health symptoms and help seeking attitude in a population-based sample in Hong Kong - Fung, Ada Wai Tung (Int J Ment Health Syst, 2021)
BACKGROUND: Mental health symptoms can be subtle, resulting in delaying treatment. A prompt identification of mental signs and symptoms is important for preventing mental disorders in the public. This study examined whether local public have adequate knowledge to identify mental health symptoms and the need to get timely professional help. METHODS: The population-based telephone surveys were conducted in 2015 and 2018. It involved a random sample of 4033 respondents aged 12–75 years. Mental health knowledge and help seeking attitude were assessed using six vignettes depicting subtle and obvious symptoms of anxiety disorders, mixed anxiety and depressive disorders, and dementia. Logistic regression models were performed to examine association between mental health knowledge and help-seeking attitude. RESULTS: Individuals with poor knowledge in subtle symptoms were more likely to be males (t =  − 5.0, p < .001), younger (F = 15.0, p < .001), have tertiary education (F = 15.0, p < .001), and employed (t =  − 2.1, p = .037). The knowledge scores of subtle and obvious symptoms were 1.5 and 2.3 respectively. Binary logistic regression found that poor knowledge of subtle symptoms was associated with reluctance to professional help seeking. CONCLUSIONS: Poorly identified subtle mental health symptoms is a major barrier to early professional help in highly educated working males. Future research should explore specific interventions to increase knowledge and professional help seeking in this group.